Development of a Model of Participation for the Local Administrative Organization for Disease Prevention and Health Hazard Control - สุวรรณบงกช, ประภัสสร; ด่านไพบูลย์, อนงค์ศิลป; วิบุลสันติ, เสาวนีย์; นาคกลิ่นกูล, สมศักดิ์ (Disease Control Journal, 2009)
A participatory action research was conducted to develop a participation model of disease prevention and health hazard control for local administrative organization (LAO). Knowledge management techniques, such as a knowledge sharing method, story telling, and an action review technique were applied to build a community participatory process. Three LAOs were purposively selected into the study including Tasai subdistrict administrative organization in Chiang Rai, U-mong sub-district municipal in Lumphun, and Maelai sub-district municipal in Prae. The research were conducted during October 2007 to September 2008. Interpretation of Qualitative data those were derived from during-action and after-action reviews, participant observation, and note taking were presented. Results showed that three participation models of disease prevention and health hazard control were developed by LAOs. The first was a reduction in the insecticide use in agricultural products of Tasai subdistrict administrative organization. The second was an air pollution mitigation in U-mong sub-district municipal. The third was a diabetes and hypertension prevention program by Maelai sub-district municipal. There were four steps of the model development: 1) preparation and community selection, 2) capacity building of team leader as facilitators, 3) identification of health issues and project planning and implementation by community participation process, and 4) action review and evaluation. Characteristics of community participation encompassed data provision, a model planning, and joint implementation. However, there were only community leaders and LAO leaders participating in the process. These could affect the sustainability of the program when they were no longer in the position. The LAOs in the research were selected according to their existing health policy and readiness. The results therefore could be a guide to aid other locales that had a similar setting to develop the participation model. However, more information was required, particularly in the certain community. In addition, the duration of study was also necessary for the community to have step-by-step learning and should be, if possible, in accordance with the term of the LAO's administrative team being in its position.